The zooecological remediation of technogen faulted soil in industrial region of Ukraine steppe zone - Pakhomov, Olexandr; Kul'backo, Yuriy; Didur, Oleg; Loza, Iryna (Acta Agraria Debreceniensis, 2010)
In Ukraine’s Steppe zone the extraction of minerals is important. To eliminate the consequences of coal mining the agricultural recultivation of the disturbed soil is used. Thus toxic compounds for human beings and the majority of plants and soil biota representatives, which can be found mining rock, get into plants and invertebrates by trophy chains. When remediating soil, it is necessary to create tropic conditions in order to provide the life of soil biota. Earthworms (Lumbricidae) are the primary decomposers of the organic material. They are numerous in soil and facilitate the improvement of natural and artificially created soil. This paper studies the possible influence of different variants of substrates, which are used in re-cultivation, the leaf litter from leaves of different wood species, as well as different levels of humidity on the representatives of soil saprophages. Optimal variants of artificial mixed-soil providing the stable existence of animals have been shown, which are recommended for the implementation of rehabilitation measures.